Geographies of science - Meusburger, Peter; Livingstone, David N.; Jöns, Heike (Knowledge and space, 2010)
This collection of essays aims to further the understanding of historical and contemporary geographies of science. It offers a fresh perspective on comparative approaches to scientific knowledge and practice as pursued by geographers, sociologists, anthropologists and historians of science